Safety and Feasibility of Photodynamic Therapy for Ablation of Peripheral Lung Tumors. Issue 2 (15th April 2023) - Bansal, Sandeep; Bechara, Rabih I.; Patel, Jiten D.; Mehta, Hiren J.; Ferguson, J. Scott; Witt, Benjamin L.; Murgu, Septimiu D.; Yasufuku, Kazuhiro; Casal, Roberto F.
Abstract : Background: Newer navigational bronchoscopy technologies render peripheral lung lesions accessible for biopsy and potential treatment. We investigated whether photodynamic therapy (PDT) delivered via navigational bronchoscopy is feasible and safe for ablation of peripheral lung tumors. Methods: Two studies evaluated PDT in patients with solid peripheral lung tumors followed by clinical follow-up (nonresection study, N=5) or lobectomy (resection study, N=10). Porfimer sodium injection was administered 40 to 50 hours before navigational bronchoscopy. Lesion location was confirmed by radial probe endobronchial ultrasonography. An optical fiber diffuser was placed within or adjacent to the tumor under fluoroscopic guidance; laser light (630 nm wavelength) was applied at 200 J/cm of diffuser length for 500 seconds. Tumor response was assessed by modified Response Evaluation Criteria in Solid Tumors at 3 and 6 months postprocedure (nonresection study) and pathologically (resection study). Results: There were no deaths, discontinuations for adverse events, or serious or grade ≥3 adverse events related to study treatments. Photosensitivity reactions occurred in 8 of 15 patients: 6 mild, 1 moderate, 1 severe (elevated porphyrins noted in blood after treatment). Among 5 patients with clinical follow-up, 1 had complete response, 3 had stable disease, and 1 had progressive disease at 6 months follow-up. Among 10 patients who underwent lobectomy, 1 had no evidence of tumor at resection (complete response), 3 had 40% to 50% tumor cell necrosis, 2 had 20% to 35%, and 4 had 5% to 10%. Conclusion: PDT for nonthermal ablation of peripheral lung tumors was feasible and safe in this small study. Further study is warranted to evaluate efficacy and corroborate the safety profile.